Letter from James Curtis Booth to Daniel M. Fox, October 20, 1886 - Booth, James Curtis (1886)
James Curtis Booth (1810-1888) writes to Daniel M. Fox (1819-1890), Superintendent of the United States Mint at Philadelphia from 1885-1890, explaining in reply to "Handy & Harman, N.Y." the conditions by which silver bars are rejected.
Keywords: Booth, James Curtis, 1810-1888; Fox, Daniel M. (Daniel Miller), 1819-1890; United States Mint; Mint of the United States